Kajian Pencantuman Keterangan Kedaluwarsa pada Label Pangan Olahan - Dyah Setyowati; Lies Sugiarti (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Expiration date is one of the information that is mandatory to be included on the processed food label. Indonesia regulates the inclusion of expiration dates with the term "best before".  One of the current world topics is food waste due to differences in understanding and inclusion of expiration date. This research aims to obtain information regarding the provisions for the inclusion of expiration date in various countries and the level of public understanding of the expiration date term. The method carried out in this research are literature study by comparing the provisions on expiration date in different countries and survey with a questionnaire. The respondents in this study were 231 respondents consisting of 78 men (33.8%) and 153 women (66.2%).  Expiration date provisions or regulations still vary in various countries. Europe and Australia have separated provisions for expiration date information based on safety (use by date) and quality (best before date), while Singapore and the United States of America have not separated provisions for the inclusion of expiration date.  Based on the results of a random survey using a questionnaire (google form) within 1 week, 115 respondents  (49.8%)  were unable to distinguish the various expiration date terms.  Respondents who understood the expiration date mostly came from respondents with education levels of  S1, S2 and S3 i.e. 57%, 64.7%, and 60% respectively while other education levels were less than 40%. This shows that education level correlates with the level of understanding of the respondent.